2019
DOI: 10.3390/molecules24020367
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Betaine on LPS-Stimulated Activation of Microglial M1/M2 Phenotypes by Suppressing TLR4/NF-κB Pathways in N9 Cells

Abstract: Microglia mediate multiple facets of neuroinflammation. They can be phenotypically divided into a classical phenotype (pro-inflammatory, M1) or an alternative phenotype (anti-inflammatory, M2) with different physiological characteristics and biological functions in the inflammatory process. Betaine has been shown to exert anti-inflammatory effects. In this study, we aimed to verify the anti-inflammatory effects of betaine and elucidate its possible molecular mechanisms of action in vitro. Lipopolysaccharide (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 50 publications
2
57
1
Order By: Relevance
“…We found that VX765 treatment significantly inhibited microglial activation and recruitment and altered polarization by inhibiting and promoting M1 and M2 activation, respectively. This may be associated with the decrease of proinflammatory cytokines and the increase of anti-inflammatory cytokines [65]. In conclusion, we demonstrated that VX765 regulated the polarization direction of microglia and the severity of pyroptosis by changing the expression of pro-and anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 51%
“…We found that VX765 treatment significantly inhibited microglial activation and recruitment and altered polarization by inhibiting and promoting M1 and M2 activation, respectively. This may be associated with the decrease of proinflammatory cytokines and the increase of anti-inflammatory cytokines [65]. In conclusion, we demonstrated that VX765 regulated the polarization direction of microglia and the severity of pyroptosis by changing the expression of pro-and anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, TLR4 could activate the downstream IκB kinase (IKK) complex, and then phosphorylate IκB, an NF-κB inhibitor that could prevent nuclear translocation of NF-κB. Upon phosphorylation, IκB was degraded and released NF-κB, which then entered nucleus and mediated the expression of in ammatory cytokines [32,33]. In the present study, we found that the expression of TLR4, MyD88, p-NF-κB p65, p-IκBα and p-IKKα/β in breast cancer cells was signi cantly down-regulated after AT-I treatment.…”
Section: Discussionmentioning
confidence: 99%
“…So far, there is still a lack of effective treatment for NP [3,4]. Microglia, the resident macrophage cells of the central nervous system, has been shown to mediate neuroinflammation [5]. Microglia activation and subsequent pro-inflammatory responses play an important role in the development of NP [6].…”
Section: Introductionmentioning
confidence: 99%
“…The M1 phenotype is characterized by increased expression of several proteins including inducible NO synthase (iNOS) and CD68, as well as increased secretion of several proinflammatory factors such as interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α [7,8]. The M2 phenotype is characterized by increased expression of several proteins such as arginase-1 (Arg-1) and mannose receptor (MR/CD206), as well as increased production of antiinflammatory cytokines such as IL-4 and IL-10 [5,9]. The microglial polarization toward the pro-inflammatory M1 phenotype often occurs during NP.…”
Section: Introductionmentioning
confidence: 99%